Border Crossing and the Logics of Space: A Case Study in Pro-Environmental Practices - Uzzell, David; Räthzel, Nora (Frontiers in Psychology, 2018)
We investigate whether and how workers in a transnational oil corporation carry practices, meanings, and identities between work and home, focussing on environmental and health and safety practices, in order to understand the larger question, how can environmentally relevant practices be generalised in society at large? Our theoretical starting point is that societal institutions function according to different logics (Thornton et. al. 2012) and the borders (Clark 2012) between these institutions create affordances and constraints on the transfer of practices between these places. By connecting these theoretical ideas, we suggest that these provide an alternative critique and explanatory account of the transfer of environmental practices between home and work than a ‘spillover’ approach. We employ life history interviews to explore the development and complexity of the causes, justifications and legitimations of people’s actions, social relationships and the structural constraints which govern relationships between these spaces. While Clark’s concepts of permeable, strong, or blended borders are useful heuristic tools, people may simultaneously strengthen, transgress or blend the borders between work and home in terms of practices, meanings, identities or institutional logics. Individuals have to be understood as mediators of the border crossing process. For environmental practices to travel from work to home they need to become embedded in a company culture that allows their integration into workers’ identities.